Improved pharmacokinetics of HIV-neutralizing VRC01-class antibodies achieved by reduction of net positive charge on variable domain - Young D. Kwon; Amarendra Pegu; Eun Sung Yang; Baoshan Zhang; Michael F. Bender; Mangaiarkarasi Asokan; Qingbo Liu; Krisha McKee; Bob C. Lin; Tracy Liu; Mark K. Louder; Reda Rawi; et al. (Taylor & Francis Group, 2023)
ABSTRACTThe amino-acid composition of the immunoglobulin variable region has been observed to impact antibody pharmacokinetics (PK). Here, we sought to improve the PK of the broad HIV−1-neutralizing VRC01-class antibodies, VRC07-523LS and N6LS, by reducing the net positive charge in their variable domains. We used a structure-guided approach to generate a panel of antibody variants incorporating select Arg or Lys substituted to Asp, Gln, Glu, or Ser. The engineered variants exhibited reduced affinity to heparin, reduced polyreactivity, and improved PK in human FcRn-transgenic mice. One variant, VRC07-523LS.v34, with three charge substitutions, had an observed in vivo half-life and an estimated human half-life of 10.8 and 60 days, respectively (versus 5.4 and 38 days for VRC07-523LS) and retained functionality, neutralizing 92% of a 208-strain panel at a geometric mean IC80 <1 µg/mL. Another variant, N6LS.C49, with two charge substitutions, had an observed in vivo half-life and an estimated human half-life of 14.5 and 80 days (versus 9.0 and 44 days for N6LS) and neutralized ~80% of 208 strains at a geometric mean IC80 <1 µg/mL. Since Arg and Lys residues are prevalent in human antibodies, we propose substitution of select Arg or Lys with Asp, Gln, Glu, or Ser in the framework region as a general means to improve PK of therapeutic antibodies.